Virtual clinical excursions--general hospital for Potter and Perry, Stockert, and Hall, fundamentals of nursing - Potter, Patricia Ann (Elsevier Saunders, 2013)
Safely practice patient care and perfect your critical-thinking skills before you begin clinical rotations with this interactive learning companion to Fundamentals of Nursing, 8th Edition! This innovative workbook/CD-ROM package lets you care for a variety of patients in a virtual multi-floor hospital, providing a hands-on learning experience in a realistic, fully immersive environment. Access and analyze information, diagnose patient conditions, set priorities, and implement and evaluate patient care - all in a true-to-life clinical setting